Pedometer-determined physical activity among primary schoolchildren in Kuala Lumpur - Wee, Bee Suan; Bulgiba, Awang; Ruzita, Abd Talib; Ismail, Mohd Noor; Poh, Bee Koon (SAGE Publications, 2019)
Objective: The aim of this study was to objectively measure physical activity and its association with sociodemographic factors among Malaysian primary school-age children. Methods: A total of 111 primary school children in Kuala Lumpur were selected through random sampling. Activity pattern was determined using pedometers and differences by sex, ethnicity and body mass index categories were analysed. The relationship between pedometer-determined physical activity and sociodemographic factors were also studied. Results: Overall, boys attained significantly higher daily step counts than girls (9573 ± 4145 vs 7313 ± 2697). Significant difference in daily step counts between boys and girls were observed during weekdays (p<0.01), weekends (p<0.05) and total mean step counts (p<0.01). Malay ethnicity showed higher daily step counts during weekdays than weekends (p<0.05). Compared with boys, girls had higher odds (OR=5.58; 95% CI 1.12, 27.77) of not meeting the recommended daily step counts. Those who had low physical activity levels had higher odds (OR=15.75; 95% CI 1.78, 139.33) of not meeting recommended daily step counts than children who had moderate physical activity level. Conclusion: Boys were significantly more active than girls and physical activity was greater during weekdays than on weekends. The primary schoolchildren in Kuala Lumpur were sedentary, with minimum physical activity being observed. Differences in sexes and physical activity levels influenced pedometer step counts in children. © The Author(s) 2019.